2018
DOI: 10.2500/aap.2018.39.4134
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of intranasal mometasone in the fixed-dose combination GSP301 versus two monotherapy intranasal mometasone formulations

Abstract: Mometasone bioavailability with GSP301 was comparable with MF-sponsor and MF monotherapies. A slightly higher Cmax was observed with GSP301 than with MF, but AUC was comparable. The addition of olopatadine to mometasone in GSP301 did not considerably affect the PK of mometasone. GSP301 was well tolerated, with only mild adverse events reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 0 publications
1
7
0
2
Order By: Relevance
“…Of the 4 SAEs that occurred during study treatment, none were considered related to treatment. These results are similar to those observed in several early clinical studies of GSP301 in patients with 22,23 and without SAR, 42,43 in another short-term phase 3 clinical study of patients with SAR, 24 and in a long-term phase 3 study of patients with PAR, 25 confirming that GSP301 has a favorable safety and tolerability profile.…”
Section: Discussionsupporting
confidence: 88%
“…Of the 4 SAEs that occurred during study treatment, none were considered related to treatment. These results are similar to those observed in several early clinical studies of GSP301 in patients with 22,23 and without SAR, 42,43 in another short-term phase 3 clinical study of patients with SAR, 24 and in a long-term phase 3 study of patients with PAR, 25 confirming that GSP301 has a favorable safety and tolerability profile.…”
Section: Discussionsupporting
confidence: 88%
“…Headache was the most commonly reported TEAE and occurred similarly across treatments (11.1% for twice-daily GSP301 and olopatadine; 8.3% for AzeFlu and placebo) except for a greater incidence in the once-daily GSP301 group (16.7%). In 2 pharmacokinetic studies of GSP301 in healthy participants, 39,40 favorable safety and tolerability profiles were observed with low systemic exposure. Furthermore, in several large, natural allergen exposure studies in SAR, once-daily or twice-daily GSP301 [30][31][32] dosing was well tolerated, with similar incidences of AEs to placebo or component monotherapies.…”
Section: Discussionmentioning
confidence: 99%
“…First results show a significant reduction of AR symptoms compared to placebo in a doubleblind pollen chamber study [64]. Studies on the phar-macokinetics of GSP301 have already shown that the fixed combination of olopatadine and mometasone is at least as readily available in a fixed combination as the mono products [65,66].…”
Section: Fixed Combination Of Topical Glucocorticoid and Intranasal Amentioning
confidence: 98%